Choosing classrooms: a structured interview on children's right to participate - Correia, N.; Aguiar, C. (International Journal of Educational Research, 2017)
Discourses from distinct areas of knowledge converge on the relevance of listening to children's perspectives on their everyday lives and, specifically, in early childhood settings. Although children's participation is considered an important criterion to assess preschool settings’ quality, there is little empirical evidence on children's ideas in these settings. This study aims to develop and pilot a structured interview to assess children's conceptions, expectations, and perceptions about participation. Results suggest children consider they have more opportunities to make choices in the classroom characterized by the participation narrative. Furthermore, the participation classroom is consistently described as the one in which children would feel better, have more fun, and like the most, suggesting children value more classrooms in which participation occurs.